Presumptions of promiscuity: reflections on being a widow or divorcee from three Indonesian communities. Issue 128 (2nd January 2016) - Mahy, Petra; Winarnita, Monika Swasti; Herriman, Nicholas
ABSTRACT: This article is concerned with a pervasive gender stereotype within Indonesian society, that of janda, meaning both widows and divorcees. The term janda is no neutral signifier of marital status, but rather carries a bundle of pejorative meanings concerned with status and presumed sexual availability to men. It is bound up within assumptions about the normality of heterosexual marriage in Indonesia, and in many ways janda is the antithesis of the ideal of ibu, meaning a virtuous wife and mother. Based on ethnographic fieldwork conducted by each of the three authors, the article examines the reproduction and effects of this stereotype in three Indonesian communities; a village in East Java, a mining town in East Kalimantan and among Indonesian expatriates in Perth, Australia. Using this multi-sited and multi-positioned material we reflect on the everyday lived experience of being a janda, in particular how the stereotype affects social status, livelihood opportunities and modes of representing oneself within a particular community.